Simulasi Montecarlo pada Penjadwalan Preventive Maintenance Komponen Kritis Mesin Breaker dan Mesin Hammermill - Wresni Anggraini; Arfan Aditia (UIN Sultan Syarif Kasim Riau, 2016)
PT. P & P Bangkinang is a company engaged in the processing of raw rubber into semi-finishedproducts (Crumb Rubber). In 2014, the company facing 280.06 hours downtime which occurred on thebreaker and hammermill machines. All along, the company implemented breakdown maintenancesystems. Under this system, if there was a problem in one machine, all other machines would be stoppedprocessing. It meant all the production process was stopped. The production process would be continuedif the machine has already fixed. The longer time to fix the machine, the longer time the productionprocess would be canceled. Machine's downtime was causing unachievement of production target. It’sonly able to achieve 86.33% from the target has been determined. The purposes of this research are todetermine the critical components of breaker and hammermill machines which causing breakdown, topropose schedule for critical component replacement, and to make monte carlo simulation for the criticalcomponents replacement schedule.The results obtained for the determination of the critical componentsas well as with the proposed scheduling replacement of components, namely small gear 492.616 hours,kelahar 727 hours, 398 hours bearing and conveyor kelahar 406.674 hours. Based on the results ofrunning time simulation for 4382 hours, appropriate strategies to minimize downtime that scenario 2(Preventive Maintenance) with a total downtime of 32.91 hours compared to scenario 1 (CorrectiveMaintenance) of 42.49 hours and the existing scenario of 49.7 hours.Keywords: downtime, monte carlo, preventive maintenance, simulation